Exploring the influence of baseline rheumatoid factor levels on TNF inhibitor retention rate in patients with rheumatoid arthritis: a multicentre and retrospective study - Cesar Díaz-Torné; Virginia Ruiz-Esquide; Clementina López-Medina; Alejandro Balsa; Alejandro Escudero-Contreras; Rafaela Ortega-Castro; Sara Manrique-Arija; Chamaida Plasencia-Rodríguez; Natalia Mena-Vazquez; Ana Martínez-Feito; Jerusalem Calvo-Gutiérrez; M Carmen Ábalos-Aguilera; et al. (RMD Open)
Objective To assess whether the retention rate of certolizumab pegol (CZP) was longer than that of other tumour necrosis factor inhibitors (TNFi) based on baseline rheumatoid factor (RF) levels.Methods Longitudinal, retrospective and multicentre study including patients with RA who were treated with any TNFi (monoclonal antibodies (mAB), etanercept (ETA) or CZP). Log-rank test and Cox regressions were conducted to evaluate the retention rate in the three groups according to the level of RF, with the third quartile of the baseline levels used as cut-off: <200 (<Q3) and ≥200 (≥Q3) IU/mL. A sensitivity analysis matching patients using a propensity score technique based on age, concomitant use of methotrexate and previous targeted synthetic/biological disease-modifying antirheumatic drugs was performed to address the imbalance across groups.Results A total of 638 individuals and 752 treatments (132 CZP, 439 mAB and 181 ETA) were included. In non-naïve patients with ≥200 IU/mL of RF, those treated with CZP showed a significantly longer retention rate in comparison with mAB and ETA. After matching using the propensity score, patients with ≥200 IU/mL RF levels exhibited longer retention rates with CZP than with mAB (HR 2.3 (95% CI 1.2 to 4.3), or ETA (HR 2.8 (95% CI 1.5 to 5.2). No differences were found between groups in patients with <200 UI/mL.Conclusions CZP showed a longer retention rate than mAB and ETA in patients with very high RF levels (≥200 IU/mL), while these differences were absent in patients with <200 IU/mL levels. The results suggest the potential effect of RF on binding the fragment crystallisable portion of certain TNFi.